Momelotinib Usage Within Our Current Canadian Myelofibrosis Armamentarium (Canadian Hematology Today, 2025)
Myelofibrosis (MF) can be categorized as primary MF (PMF), or secondary MF, which comprises post-polycythemia MF (PPV) and post-essential thrombocythemia (PET). Activating mutations in JAK2, CALR, or MPL are the main driver mutations resulting in abnormal signalling that promotes cell proliferation and survival, leading to secretion of inflammatory cytokines causing myeloproliferation, bone marrow fibrosis, and extramedullary hematopoiesis in MF.The current treatment landscape for MF consists of strategies to reduce spleen volume and improve MF-related symptoms with less effective results in improving cytopenias. Mainstay therapies have included hydroxyurea (HU) and Janus kinase inhibitors (JAKi), as well as curative allogeneic stem cell transplant (ASCT), though fewer patients are eligible for this treatment. Several JAKi have been approved in Canada for first-line treatment, including ruxolitinib, fedratinib, and most recently, momelotinib. Approximately 40% of patients with MF have anemia at diagnosis, and nearly 25% are red blood cell (RBC) transfusion-dependent (TD). Many patients with MF struggle with symptoms related to chronic anemia, and anemia often progresses with time, leading to transfusion dependence for many patients. Anemia of any severity negatively impacts MF survival and is highlighted as a negative prognostic factor among most validated MF scoring systems. Anemia results in increased patient fatigue and lower quality of life (QoL), which results in increased healthcare utilization. Severe anemia results in a 2-fold increased healthcare resource utilization compared to mild anemia. This review focuses on the current treatment approaches for MF, with particular focus on MF-related anemia and the targeted role of newer JAKi, such as momelotinib.